Distribution of Health Property before the Heavier Dies - Anita Putri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The distribution of inheritance by heirs to heirs before the heir dies in the community is a customary and customary way of distributing inheritance to their children as heirs in the hope of getting benefits for children in supporting economic needs and avoiding conflicts in the family. The results show that The distribution of inheritance before the heir dies in the community in terms of Islamic law is a gift giving because in Islamic law inheritance occurs because of the principle of death. And the reason parents share inheritance during their lifetime is as a form of parental love for their children and is the initial capital for their children's lives in the future.